Effect of web conferring on Social Presence in a Face-to-face choral ensemble class. Issue 2 (1st October 2014) - Stover, Sheri; Hambright, Grant; Collins, Drew
Classes where students have opportunities to interact with experts allow students to apply what they have learned and begin to contextualize the content learned in class. The instructor in this face-to-face choir ensemble class used web conferencing to set up a virtual interview with an expert, Dr David Dickau, to allow his students to have the opportunity to have direct contact with a living composer whose music has had a profound influence in the choir ensemble field. The interactive web conference included an interview with the composer, followed by a critique of the choir's performance of his composition, 'If Music Be the Food of Love'. Students completed a survey following the web conference session. This study examines the effect of the composer's virtual visit on students' understanding and performance of his song. It also looks at students' recommendations to continue such virtual activities as well as the effect on Social Presence. Results of this case study show that Dr Dickau's virtual visit had an overwhelmingly positive effect on all of these areas and students strongly recommended the continuation.